PENGARUH BRAND EXPERIENCE DAN BRAND PERSONALITY TERHADAP REPURCHASE INTENTION PRODUK ESQA COSMETICS - Kustiwan, Choirunnisa Luthfiyah; Rubiyanti, Nurafni (Business Administration Department - Universitas Katolik Parahyangan, 2024)
The cosmetics market is growing rapidly with innovation, influenced by lifestyle trends. Dependence on the use of cosmetics has become a daily habit, especially for generation Z women, who are considered important by the environment around them. This research aims to determine the influence of brand experience and brand personality on repurchase intention for ESQA Cosmetics. The research method used in this research is a quantitative method with a descriptive-causality type of research. Sampling was carried out using a non-probability sampling technique used, namely purposive sampling, a total of 346 consumer respondents who had used or purchased ESQA Cosmetics products among generation Z in Bandung City. The data analysis technique used was descriptive analysis and multiple linear regression analysis. The results of this research show that there is a significant influence between brand experience on repurchase intention on ESQA products and there is a significant influence between brand personality on repurchase intention on ESQA Cosmetics. Then brand experience and brand personality simultaneously have a significant effect on repurchase intention at ESQA Cosmetics. The contribution of influence from the brand experience and brand personality variables influences the dependent variable repurchase intention.